Flood Vulnerability Analysis Based on GIS and Remote Sensing at Silat Hulu - Purwanto, Ajun; Andrasmoro, Dony; Eviliyanto, Eviliyanto (Indonesian Journal of Geography, 2024)
A flood is a natural disaster that may happen anywhere and anytime. These disasters have become an annual cycle in Indonesia, and it is important to be swift in their mitigation and control. This study aims to determine the vulnerability of flooding in Silat Hulu and the extent of the area likely to be submerged. The method used was survey and secondary interpretation data. Data was from topographic maps, Sentinel 2A images, and 10 x 10 m resolution DEM images acquired on November 21, 2021, obtained from the ALOS PALSAR imagery. Data analysis using ArcGIS 10.8, using the weighted overlay spatial analysis tool. The results showed that the study location had three flood vulnerability classes: low, medium, and high. The locations with low vulnerability classes have an area of 2,921 ha, moderate have 32,683 ha, and high have 28,208 ha. Low flood vulnerability is spread to a small extent in Nangau Luan, Nangau Lungu, and Landau Badai villages. The level of vulnerability is mostly in Nangau, Nangau Lungu, and Landau Storm. The high level of vulnerability is mainly spread in the villages of Nangau Dangkan, Blimbing, Nangau Ngeri, and Nangau Lungu. GIS and remote sensing approaches are practical tools for flood-prone maps. Furthermore, GIS-based flood vulnerability mapping and remote sensing are valuable tools for estimating flood vulnerability areas.